Características y secuencia evolutiva de las acumulaciones cuaternarias del río Ebro en el sector de La Zaida-Mequinenza (prov. Zragoza) - Julián Andrés, Asunción; Chueca Cía, Javier (Geographicalia, 2017)
This work presents the Quaternary evoolutional patterns of an Ebro’s river sector in which the channel adopts a morphology in entrenched meanders. The morphology, topography and sedimentological aspects of its terraced (9 levels) fluvial deposits, vestige of different quaternary accumitlative phases, are analysed. Besides, the correlation of this sector with other Ebro river sectiors and some of its fluvial tributaries (Cinca and Segre rivers, basically), is stablished.